Science World [motion pictures] Ecology : grasslands; - gropical rain forest; - desert; - tundra. (Coronet/MTI Film and Video, 1989)
Science World ... journeys from depths of the ocean to the outer reaches of the galaxy. Spectacular photography in award-winning programs expolres the basic framework of our world.